Efficacy and safety of a novel beclomethasone dipropionate dry powder inhaler (Clickhaler) for the treatment of adult asthma. Amsterdam Clinical Study Group. - Stradling, JR; Pearson, MG; Morice, A; Peake, MD; Barnes, N (2000)
A randomized, double-blind, double-dummy protocol was used to compare the safety and efficacy of beclomethasone dipropionate (BDP) delivered by a novel dry powder inhaler (DPI, Clickhaler) or by a pressurized metered-dose inhaler (MDI) plus spacer. There was a four-week run-in period, completed by 240 adult patients, who received BDP via an MDI. Patients with stable asthma were then randomized into a 12-week treatment period and received BDP (< or =2 mg/day via DPI or MDI). There were no significant differences in morning peak expiratory flow (PEF) (primary endpoint), evening PEF, overall daytime or nighttime symptom scores, or lung function parameters (forced expiratory volume in 1 sec, forced vital capacity) between DPI and MDI. The safety profiles were similar and patient acceptability for Clickhaler was high. In conclusion, BDP administered via Clickhaler was found to be clinically equivalent to an optimally used MDI. Patients with stable asthma currently receiving BDP via MDI may be effectively switched to treatment via Clickhaler DPI.